Do Servant Leadership Works in Police Departement? - Sitepu, Rismawati; M. Said, Ilham (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
In Servant leadership research there are 2 Gabs found here: 1) Servant Leadership cannot thrive in a hierarchical, authoritarian organization. 2) The second Gab, namely Servant Leadership, is rarely studied in the police field, research in the International Scopus Journal on Servant Leadership in the Literature Rivew System (1998-2018). The purpose of this study is to explore how servant leadership can be applied to the police department, because there was a previous study (wong page 2003) which stated that servant leadership could not be applied to the hierarchical structure of the bureaucracy. Design/methodology/approach-This qualitative research uses a narrative inquiry method within the framework of interpretive phenomenological analysis (Smith et al., 2009) to capture the experience of the task undertaken by the lead informant, namely the Key Informan at the Head of the Human Resources Bureau consisting of: 1) Head Planning and Administration Section (subbagrenmin), 2) Personnel Control Section (Bagdalpers); 3) Career Development Division (Bagbinkar); 4) Personnel Care Division (Bagwatpers); and 5) the Psychology Section (Bagpsi) of the East Java Regional Police. Finding :These studies show that servant leadership is found in hierarchical organizations,Contribution:The Regional Police of the East Java Region (POLDA JATIM) has become a model in advancing the Police throughout Indonesia, by showing: keep a smile, the reality of solid interactions between leaders and members (not rigid,intimacy), work with joy, member character becomes servant, member empowerment through find potential talent of members